Mangrove Biodiversity for Coastal Resilience and Sustainability: A Dynamic Case Study from Indonesia - Nana Kariada Tri Martuti; Abdul Jabbar; Andin Irsadi; Wahid Akhsin Budi Nur Sidiq; Inaya Sari Melati; Amar Sharaf Eldin Khair; Dhita Pracisca Mutiatari (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Mangrove degradation and socio-economic vulnerability in the Kendal coast require an integrated approach. The study used ecological surveys (mangrove vegetation analysis, avifauna) and socio-economic (n=186 households). Integrated Coastal Management (ICM) analysis and model were developed using a dynamic approach, encompassing problem identification, conceptual model formulation, and validation preparation. 14 mangrove species (H' index = 1.58–1.80) and 61 bird species (H' = 3.50) were found. Community participation reached 97%, but women's participation was only 3%, with 58% of households being landless and 61% unproductive land. Infrastructure was severely damaged (36% of roads) and 97% of the area was flooded. The dynamic model of ICM in Kendal Regency highlighted coastal biodiversity conservation, enhanced community capacity and participation, and secure land ownership as the primary drivers of sustainable coastal governance. Despite ongoing pressures from coastal hazards and urban expansion, biodiversity conservation remained the pivotal intervention, sustaining ecosystem integrity, improving household incomes, and reinforcing socio-economic resilience through positive feedback loops within the coastal social–ecological system.